Does the central supporting policy for resource-exhausted cities improve carbon efficiency? Evidence from a quasi-natural experiment in China - Yiwen Peng; Weihua Yu (Journal of Government and Economics (JGE), 2025)
Promoting the carbon efficiency is an accepted issue in China's sustainable development against the background of carbon neutrality. In order to help China's resource-exhausted cities overcome their difficulties, the central government has issued an official policy document titled Opinions of Promoting the Sustainable Development of Resource-based Cities, which has announced 69 resource-exhausted cities. The central and local governments have strengthened policy and funds support to set up a long-term mechanism of sustainable development. This paper utilizes a spatial difference-in-difference (SDID) method to investigate how the supporting policy affects carbon performance in those resource-exhausted cities and their neighboring cities, with city-level data from 2004 to 2016. The results show a positive feedback of supporting policy on carbon performance in both local regions and adjacent regions. Furthermore, we find that wage distortion could account for carbon performance improvement. Our results provide evidence for realizing the low-carbon economy of resource-exhausted cities in China.
Keywords: 330; Carbon efficiency; Low-carbon economy; Spatial difference-in-difference model; Wage distortion